Doping-Induced Anisotropic Self-Assembly of Silver Icosahedra in [Pt2Ag23Cl7(PPh3)10] Nanoclusters - Bootharaju, Megalamane S; Kozlov, Sergey M; Cao, Zhen; Harb, Moussab; Maity, Niladri; Shkurenko, Aleksander; Parida, Manas R; Hedhili, Mohamed N; Eddaoudi, Mohamed; Mohammed, Omar F; Bakr, Osman M; Cavallo, Luigi; et al. (Journal of the American Chemical Society, 2017)
Atomically precise self-assembled architectures of noble metals with unique surface structures are necessary for prospective applications. However, the synthesis of such structures based on silver is challenging because of their instability. In this work, by developing a selective and controlled doping strategy, we synthesized and characterized a rod-shaped, charge-neutral, diplatinum-doped Ag nanocluster (NC) of [Pt2Ag23Cl7(PPh3)10]. Its crystal structure revealed the self-assembly of two Pt-centered Ag icosahedra through vertex sharing. Five bridging and two terminal chlorides and 10 PPh3 ligands were found to stabilize the cluster. Electronic structure simulations corroborated structural and optical characterization of the cluster and provided insights into the effect of the Pt dopants on the optical properties and stability of the cluster. Our study will open new avenues for designing novel self-assembled NCs using different elemental dopants.